Covid-19 pandemic impacts on essential transit riders: Findings from a U.S. Survey. (April 2022) - He, Qian; Rowangould, Dana; Karner, Alex; Palm, Matthew; LaRue, Seth
Highlights: A national survey of public transit users during the Covid-19 pandemic in the U.S. Vehicle access is associated with reduced transit trips. Reasons for stopping/reducing transit use map onto social vulnerabilities. Essential destinations became harder to reach for several groups. Transit finance policy must prioritize service for those who need it most. Abstract: The Covid-19 pandemic has decimated public transit service across the United States and caused significant decreases in ridership. Little is known about the reasons for unevenness in pandemic-era mode shifts and the impacts of pandemic-related transit reductions on riders' day-to-day lives. Using a national survey of U.S. transit riders (n = 500) conducted in fall 2020, this study examines changes in transit use since the pandemic began, the reasons for transit reductions, and the effects of reduced transit use and transit service on transit riders' ability to meet their travel needs. The Covid-19 pandemic has exacerbated existing transportation burdens for those who have limited mobility options, those facing socioeconomic challenges, Hispanic or Latinx riders, and female, non-binary or genderqueer people. We close with recommendations for strengthening transit service for these groups in the long term as we recover from the pandemic.